Growth and fluctuation in the world economy, 1870-1960 - MADDISON, A. (PSL Quarterly Review, 2014)
The present study puts the post-war acceleration of growth in world trade in historical perspective and relates it to movements in income. In particular, the author analyses the interaction between the industrialized countries of Europe and America in the process of generating growth and fluctuations in the world economy. New estimates are presented of the value and volume of world trade, as well as figures for major countries and regions that have not hitherto been readily available in a comparable form. Estimates are also presented on the long-term growth of income in all the main industrial countries. JEL: F10, F20